Spatio‐Temporal Patterns of Open Surface Water in the Central Valley of California 2000‐2011: Drought, Land Cover, and Waterbirds1. (18th September 2015) - Reiter, Matthew E.; Elliott, Nathan; Veloz, Sam; Jongsomjit, Dennis; Hickey, Catherine M.; Merrifield, Matt; Reynolds, Mark D.
Abstract: We used Landsat satellite imagery to (1) quantify the distribution of open surface water across the Central Valley of California 2000‐2011, (2) summarize spatio‐temporal variation in open surface water during this time series, and (3) assess factors influencing open surface water, including drought and land cover type. We also applied the imagery to identify available habitat for waterbirds in agriculture. Our analyses indicated that between 2000 and 2011 open surface water has declined across the Central Valley during the months of July‐October. On average, drought had a significant negative effect on open surface water in July, September, and October, though the magnitude and timing of the effect varied spatially. The negative impact of a drought year on open water was experienced immediately in the southern Central Valley; however, there was a one year time‐lag effect in the northern Central Valley. The highest proportion of open surface water was on agricultural lands followed by lakes, rivers, and streams, yet the relative proportions varied spatially and across months. Our data were consistent with previous descriptions of waterbird habitat availability in post‐harvest rice in the northern Central Valley. Tracking water distribution using satellites enables empirically based assessments of the impacts of changing water policy, land‐use, drought, climate, and management on water resources.